Personal Branding Beauty Vlogger (Studi Deskriptif pada Channel Youtube Tasya Farasya) - Amier, Helmawati; Sopacua, Yustina; Alfredo, Ronald (Jurnal Ilmu Komunikasi Pattimura, 2023)
The purpose of this study is to describe how personal branding was built by Tasya Farasya though video on her Youtube channel. This research is a qualitative descriptive study that aims to describe how the personal branding of a beauty vlogger Tasya Farasya through her youtube channel. And to find out what are the indicators needed to build personal branding based on what was stated by Peter Montaya. Primary data is done through video objects on Tasya Farasya’s youtube channel, which sees the number of viewers(viewers), likes (likes), and comments (comments) on several predetermined videos, while seconday data retrieval is done through several sources. Taken from online media related to Tasya Farasya’s youtube beauty vlogger channel. The results of this study found that the personal branding that was formed by Tasya Farasya through the content on her Youtube video channel was judged to be in accordance with eight predetermind indicators, namely specialization, personality, perseverance, good name, leadership, appearance, unity, and difference. It can be concluded that Tasya Farasya displays all the indicators of the formation of personal branding in the video content on her youtube channel so that she can maintain the personal branding she has created.